Pengaruh Lama Penyimpanan Terhadap Kadar Hemoglobin pada Komponen Packed Red Cell yang Ditambahkan Antikoagulan CPDA(1) - Nurhamida, Trinida; Baehaki, Farhan (Jurnal Kesehatan Rajawali, 2024)
Packed Red Cell (PRC) is generally used for the blood transfusion process. The quality of PRC is closely related to its storage time. To maintain the quality of PRC, an anticoagulant is usually added, such as CPDA(1), which can maintain the quality of PRC for up to 35 days. However, within this time period it is necessary to check the components in the PRC. This study aims to determine the effect of storage time on hemoglobin levels in PRC added with the anticoagulant CPDA(1). This research is an observational study using a cross sectional design. The samples used were 20 flasks of PRC blood at the Majalengka Regional Hospital Blood Bank to which the anticoagulant CPDA(1) was added. Hemoglobin levels were measured every seven days for up to 35 days using a Sysmex XN-450 Hematology Analyzer. The data were analyzed descriptively to determine the characteristics of the data and analyzed statistically using the One Way Anova Test to determine the effect of storage time on hemoglobin levels. The results of the study showed that the average hemoglobin levels in PRC from week zero to week five were respectively 21.85 g/dL, 22.35 g/dL, 22.84 g/dL, 23.55 g/dL, 24.27 g/dL, and 24.99 g/dL. The results of statistical analysis also showed a significant effect with a significant increase in hemoglobin levels from week 0 to week 5. So, it can be concluded that storage time is one of the factors that must be considered to maintain the quality of PRC.